Perancangan Sistem Informasi Posyandu Lansia Berbasis Website Untuk Optimalisasi Pelayanan Kesehatan Masyarakat - Adistiani Shafanissa Azzahra; Rahadian Kurniawan (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
The Elderly Health Post Information System is an information system that leverages information and communication technology to address issues associated with manual data reporting. The manual method involves recording and collecting data using a large ledger, which is then processed and reported to the Community Health Center. Accuracy and precision in data collection are crucial for providing valid and up-to-date health information to the community. The development of the information system for the Elderly Health Post aims to streamline the processes of recording, processing, and reporting activity data for the Elderly Health Post Matahari. This system will utilize the MySQL database and the PHP programming language. Through the implementation of this information system, the expectation is that the Posyandu implementation process will become more efficient and accurate. This information system will be constructed using the PHP programming language (Hypertext Preprocessor), Hypertext Markup Language (HTML), and Cascading Style Sheet (CSS) for the presentation style. Additionally, MySQL will serve as the database, and the development methodology will follow the waterfall approach.